Q: How do you factor 12y squared plus 11y plus 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

23y-11y = 12y

y(3y^2 - 12y + 4)

2y2 + y = -11yAdd 11y to each side of the equation:2y2 + 12y = 0Divide each side by 2:y2 + 6y = 0Factor the left side:y (y + 6) = 0The equation is true if either factor is zero:y = 0or (y + 6) = 0y = -6

Pull out the common factor of 2 ... 2(y^2+6y-16) Then just factor (y^2+6y-16) ... (y-2)(y+8)

4(3y+4)

Related questions

23y-11y = 12y

y(3y^2 - 12y + 4)

Y=10

(x + 11y)(x - 12y)

(x + 15)(x - 3)

2y2 + y = -11yAdd 11y to each side of the equation:2y2 + 12y = 0Divide each side by 2:y2 + 6y = 0Factor the left side:y (y + 6) = 0The equation is true if either factor is zero:y = 0or (y + 6) = 0y = -6

12y3 - 30y2 + 12yFactor out a y:y(12y2 - 30y + 12)Factor out a 6:6y(2y2 -5y + 2)Factor 2y2 - 5y + 26y(2y - 1)(y - 2)

12Y + 9 all I can see to factor out is 3 3(4Y + 3)

#

5x=11y

4x + 12y = 4(x + 3y)

Pull out the common factor of 2 ... 2(y^2+6y-16) Then just factor (y^2+6y-16) ... (y-2)(y+8)